Correlation between welding behavior and mechanical anisotropy of long chain polyamide 12 manufactured with fused filament fabrication. (20th January 2021) - Qi, Shunxin; Gao, Xia; Su, Yunlan; Dong, Xia; Cavallo, Dario; Wang, Dujin
Abstract: Fused filament fabricated (FFF) parts generally show anisotropic mechanical properties. Moreover, the anisotropy in FFF-printed parts varies with polymeric materials, depending on their characteristic relaxation and/or crystallization behavior. To acquire in-depth understanding of the mechanical anisotropy induced by the FFF technique, long chain polyamide 12 (PA12) was chosen for an investigation of the effect of printing temperatures on the microstructures and the mechanical properties of FFF-printed parts. It is found that increasing platform temperature gives rise to an increase in crystallinity and lamellae thickness, slightly improving the tensile strength of the PA12 parts with the deposited strands parallel to the loading direction (i.e. raster angle = 0°). Increasing nozzle temperature promotes large neck length and prolongs the weld time that permits molecular diffusion and entanglements at the weld zone. This significantly enhances the inter-filament bond quality revealed by the tensile strength of 90° specimens. Ultimately, the mechanical anisotropy of PA12 parts drops from 40% to 10%, as the nozzle temperature changes from 190 °C to 250 °C. Moreover, a power-law dependence of the mechanical anisotropy on the weld time is observed in PA12 parts. This suggests that the mechanical anisotropy of FFF-printed PA12 parts is determined by molecular diffusion at the weld zone, rather than by crystallization behavior. Graphical abstract: Image 1 Highlights: The nozzle temperature influences viscous sintering and molecular diffusion at weld zone by governing the weld time ( τ w ). The mechanical anisotropy of the PA12 parts showed a linear dependence on log τ w . The mechanical anisotropy of PA12 parts is determined by molecular diffusion at the interface, rather than crystallization.